INTEGRATION OF SOLAR POWER PLANTS AND BATTERY ENERGY STORAGE SYSTEMS FOR INDUSTRIAL ENERGY DEMAND IN REMOTE ISLAND: A CASE STUDY OF BUNYU ISLAND INDONESIA - Permana Putra Sinaga, Oddy
Bunyu Island, located in North Borneo, Indonesia, is facing increased energy demand, driven primarily by industrial growth such as from Industrial Load. The island's existing energy system, which relies heavily on Gas Engine Power Plants (PLTMG) and Diesel Power Plants (PLTD). This study explores the potential of integrating Solar Power Plants (PLTS) with Battery Energy Storage Systems (BESS) as a more sustainable energy alternative. A quick calculation method was developed to assess the feasibility of this hybrid system, with manual calculations verifying initial estimates. These calculations were further validated through simulators. The proposed system, which consist of a 26,6 MWp PLTS, 70,4 MWh battery storage, and a 25,3 MW inverter, was evaluated for both cost and performance. Although the Levelized Cost of Electricity (LCOE) for the hybrid system is higher than the current infrastructure, long-term benefits-including reduced fossil fuel consumption, lower emissions, and enhanced energy reliability-make the system a promising solution. Additionaly, the study recommends phasing out PLTD in favor of a PLTMG and PLTS+BESS hybrid system to improve the island's energy reliability. This approach can serve as a model for renewable energy integration in other remote areas across Indonesia.